PKM MENUJU UMKM EKONOMI KREATIF BERBASIS DIGITAL DIKELURAHAN PENATIH - I Putu Eka Indrawan; Ayu Aprilyana Kusuma Dewi; I Wayan Dika (Sewagati, 2023)
The empowerment of Micro, Small and Medium Enterprises (UMKMs) is one of the key aspects of local economic development in many countries, including Indonesia. To achieve the full potential of UMKM, collaboration with various agencies, such as the government, universities, and social institutions, is important. This article reviews the involvement of various parties in UMKM empowerment efforts in Penatih Village, which has implemented various activities and trainings, including UMKM workshops. The main focus of this research is digital training that is continuously conducted by PGRI Mahadewa University Indonesia, especially the Informatics Engineering and Information Systems study programs. The results of observations and evaluations of training stages 1 and 2 show that the development of UMKMs in the fields of Tedung, sculpture, and Silver by Penatih Village residents has very good prospects. Therefore, the Digital-based UMKM training phase 3 is focused on providing types of UMKMs that can be sold to people in Bali and the international market. After the training, the UMKM participants have the ability to manage their digital-based products on the Bali UMKM web.